2019
DOI: 10.3390/nu11050960
|View full text |Cite
|
Sign up to set email alerts
|

Melanocortin-4 Receptor and Lipocalin 2 Gene Variants in Spanish Children with Abdominal Obesity: Effects on BMI-SDS after a Lifestyle Intervention

Abstract: Mutations leading to a reduced function of the melanocortin-4 receptor (MC4R) exert a major gene effect on extreme obesity. Recently it was shown that the bone derived hormone lipocalin 2 (LCN2) binds to the MC4R and activates a MC4R dependent anorexigenic pathway. We identified mutations in both genes and screened the effects of MC4R and LCN2 mutations on eating behavior and weight change after a lifestyle intervention. One hundred and twelve children (11.24 ± 2.6 years, BMI-SDS 2.91 ± 1.07) with abdominal ob… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
7
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 46 publications
2
7
0
Order By: Relevance
“…In our cohort of children and adolescents with overweight or obesity, we identified 30 carriers of damaging or unresolved MC4R mutations (2.5%). Our finding is similar to the previously reported prevalence of 2.5% in a sample of Danish men with juvenile-onset obesity [ 35 ], and is in accordance with other studies in samples of European individuals with obesity reporting prevalences between 0.2 and 6.3% [ 8 , 11 , 13 , 15 , 17 , 18 , 36 , 44 ]. In comparison, the prevalence of pathogenic MC4R mutations has been estimated to be 0.15% in the general German population [ 36 ], and a similar prevalence would be expected in the Danish population.…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…In our cohort of children and adolescents with overweight or obesity, we identified 30 carriers of damaging or unresolved MC4R mutations (2.5%). Our finding is similar to the previously reported prevalence of 2.5% in a sample of Danish men with juvenile-onset obesity [ 35 ], and is in accordance with other studies in samples of European individuals with obesity reporting prevalences between 0.2 and 6.3% [ 8 , 11 , 13 , 15 , 17 , 18 , 36 , 44 ]. In comparison, the prevalence of pathogenic MC4R mutations has been estimated to be 0.15% in the general German population [ 36 ], and a similar prevalence would be expected in the Danish population.…”
Section: Discussionsupporting
confidence: 93%
“…In both studies, no significant differences in other-examined traits were identified [ 16 , 17 ]. Finally, a Spanish study described that among children with obesity, carriers of MC4R mutations (n = 8) achieved similar or greater reduction in BMI-SDS loss compared to noncarriers ( n = 103) after a short 8-week lifestyle intervention [ 18 ]. However, only some of the carriers maintained the reduction in BMI SDS after 1 year of intervention [ 18 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Few studies investigated the possible differences in response to obesity treatment between MC4R mutation carriers and noncarriers in children. Generally, the mutations do not seem to influence the effect of lifestyle interventions [16][17][18], though carriers of an MC4R mutation may have difficulties maintaining their weight loss [16]. These intervention studies have been limited by small study samples and short duration.…”
Section: Introductionmentioning
confidence: 99%
“…The diverse articles in this Special Issue highlight the complexity and extent to which nutrition and physical activity behaviors may influence different health aspects of children and adolescents. Few studies in this Special Issue combined genetic data with nutritional data [28], a likely expanding research area in the coming years, with the goal to provide personalized and gene-based dietary recommendations in the future. As seen by the various findings and recommendations, not only is more work in this area required but the translation of this work to practice and policy is imperative if we are to address the challenges impacting the nutrition, physical activity, and health of young populations.…”
mentioning
confidence: 99%